Ferroptosis Unleashed: A Bold Approach to Revolutionize Cancer Treatment - Shrabani Manna,; Ayushi Patel,; Dr. Gajendra Singh Tyagi, (Asian Journal of Pharmaceutical Research and Development, 2025)
One of the deadliest diseases that affects world health is cancer. More than one cell death pathwayhas been found, one of which is ferroptosis. In 2012, the word ferroptosis was introduced to characterize a regulated cell death dependent on iron and arising from the build-up of reactive oxygen species derived from lipids. This particular form of cell death was discovered to possess unique molecular traits that set it apart from other types of regulated cell death. Ferroptosis characteristics have been noted. These chemical characteristics have appeared on occasion during the past few decades, but it wasn't until recently that they were identified as proof of a unique type of cell death. Here, we outline the development that led to the emergence of the idea of ferroptosis, as well as the history of data consistent with its current description. We also review the latest applications and implications of ferroptotic death pathway modifications.